Scaling relative asymmetry in space syntax analysis - Mário Júlio Teixeira Krüger (2013)
This paper reports on a study of space syntax measures and focuses on the standard deviation of the depth from an axial map. The first section of the paper is a partial review of the original study 'On nodeand axial maps: Distance measures and related topics' (Krüger, 1989). The following sections present new developments whereby a more robust statistical approach to work with integration is used, which notonly considers the mean values given by Relative Asymmetry (RA), but also the corresponding standard deviation. In other words, the proposition is to work not only with a measure of centrality (1/RA), but alsowith a dispersion measure in order to obtain a more complete picture of the distribution of depth in an axial map. The result of this study on space syntax measures takes into account the standard deviation of thedepth from an axial map, proposing a new measure of Scaled Relative Asymmetry of axial line i (SRAi), which suggests powerful correlations with natural movement.